2003
DOI: 10.1046/j.1460-9568.2003.02618.x
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of α1G T‐type calcium channel gene (CACNA1G) expression during neuronal differentiation

Abstract: Down-regulation of T-type Ca channel current and mRNA occurs following differentiation of Y79 retinoblastoma cells. To understand how the decrease in expression is linked to cell differentiation, we examined transcriptional regulation of the Cav3.1 Ca channel gene, CACNA1G. We identified two putative promoters (A and B) in 1.3 kb of cloned genomic DNA. Reverse transcriptase-polymerase chain reaction and 5' rapid amplification of cDNA ends-polymerase chain reaction analyses demonstrated that two transcripts wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
29
0

Year Published

2004
2004
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(31 citation statements)
references
References 43 publications
2
29
0
Order By: Relevance
“…Scale bars, 100 m. Th, Thalamus; Rt, reticular nucleus; CA1, field CA1; DG, dentate gyrus; BLA, basolateral amygdala. The primers for the proximal region of the human (Hs) and mouse (Ms) Cacna1g promoter are numbered according to the most upstream transcription start identified experimentally in the human gene (Bertolesi et al, 2003) and predicted in Ensembl in the mouse gene. The primers for the TOP/FOP promoters are identical with the pTA-Luc (vector backbone) sequencing primers.…”
Section: Rna Isolation and Real-time Pcrmentioning
confidence: 99%
See 1 more Smart Citation
“…Scale bars, 100 m. Th, Thalamus; Rt, reticular nucleus; CA1, field CA1; DG, dentate gyrus; BLA, basolateral amygdala. The primers for the proximal region of the human (Hs) and mouse (Ms) Cacna1g promoter are numbered according to the most upstream transcription start identified experimentally in the human gene (Bertolesi et al, 2003) and predicted in Ensembl in the mouse gene. The primers for the TOP/FOP promoters are identical with the pTA-Luc (vector backbone) sequencing primers.…”
Section: Rna Isolation and Real-time Pcrmentioning
confidence: 99%
“…7C) Ϫ680/ϩ259AB, Ϫ680/ϩ83A, ϩ7/ϩ259B, and ϩ76/ϩ259B was achieved by PCR using primers identical with those used by others (Bertolesi et al, 2003), namely F23/R962, F23/R790, F708/R962, and F778/R962, respectively. The Ϫ680A/ϩ8A fragment was amplified with F23 and a new primer R727, GCCTCGAGCGAAAAGGGGGGCA.…”
Section: Rna Isolation and Real-time Pcrmentioning
confidence: 99%
“…11A for the mature, adult cochlea. Ca 2ϩ influx through low-voltage-activated T-type Ca 2ϩ channels serves multiple roles: they are responsible for spontaneous activity in neurons (Huguenard 1996;Llinás and Yarom 1981) and pacemaker cells (Hagiwara et al 1988), as well as Ca 2ϩ -dependent signaling, including cell proliferation (Rodman et al 2005a,b), differentiation (Bertolesi et al 2003;Strobeck et al 1999), and apoptosis (Wang et al 1999). We have identified and isolated a novel Ca v 3.1 channel isoform from the mouse inner ear: a splice variant that excludes exon14, exon25, exon34, and exon35, but includes exon26 and exon38 (Fig.…”
Section: Expression Of Ca V 31 Channels In the Inner Ear During Devementioning
confidence: 99%
“…Because mibefradil inhibits cell proliferation in vascular tissues and there appears to be robust expression of T-type current as cells transition from G0 to G1 and S-phase, the possibility that T-type channels could be involved in regulating cell proliferation has been raised (Bertolesi et al 2003). Localization of the Ca v 3.1 immunoreactivity to nonsensory cells of the cochlea, vestibule, and fibrocytes of the spiral ligament and limbus is striking.…”
Section: Expression Of Ca V 31 Channels In the Inner Ear During Devementioning
confidence: 99%
“…Down-regulation of Cav3.1 T-type channel activity and expression was further demonstrated to be due to a reduced activity of the promoters controlling its transcriptional expression [61]. A more recent study analysing modifications in alternative splicing showed that there is a considerable change in Cav3.1 splice variants occurring during neuronal differentiation [62].…”
Section: Expression Of Voltage-dependent Calcium Channelsmentioning
confidence: 99%